2021
DOI: 10.3390/math9222925
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Carbon Nanotube Flow near the Stagnation Region over a Permeable Vertical Plate with Heat Generation/Absorption

Abstract: This research explored the mixed convection flow past a vertical plate immersed in a hybrid carbon nanotube near the stagnation point. The hybrid carbon nanotube was synthesized by the mixture of two nanoparticles, namely multi-wall (MWCNT) and single-wall (SWCNT) carbon nanotubes immersed in water (base fluid). In addition, attractive aspects of suction/injection and heat generation/absorption effects were incorporated. Similarity variables were used to convert the partial differential equations describing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Thus, it is assured that the fluid flow and heat transfer of the current problem can be solved reliably using the present numerical method. The range of nanoparticle volume fraction (ϕ 1 , ϕ 2 ) used in this study is taken from the previous study by Anuar et al [8] which in the range of 0 ϕ 1 , ϕ 2 0.02. Next, moving parameter λ are taken over the range of −0.50 < λ < −0.40.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it is assured that the fluid flow and heat transfer of the current problem can be solved reliably using the present numerical method. The range of nanoparticle volume fraction (ϕ 1 , ϕ 2 ) used in this study is taken from the previous study by Anuar et al [8] which in the range of 0 ϕ 1 , ϕ 2 0.02. Next, moving parameter λ are taken over the range of −0.50 < λ < −0.40.…”
Section: Resultsmentioning
confidence: 99%
“…Recent experimental and numerical finding by Anuar et al [8] found that hybrid carbon nanotube had a higher rate of heat transfer when compared to carbon nanotube and conventional fluid. However, the above mentioned study is restricted to the problem in a permeable vertical plate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, ref. [32] discourse the attractive aspects of suction/injection and heat generation/absorption effects in the flow. It is noted that the suction effect and heat-absorption parameters increase the range of the solution.…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by the above aforementioned works, this paper decomposes the novelty in (i) utilizing hybrid carbon nanotubes as an essential component in improving the heat transfer effectiveness [32], (ii) adding the hydromagnetic effect for this problem due to its high potential capability especially in drug and gene delivery, cell separation and manipulation in bio-medical field [47,48], (iii) analyzing the thermal radiation effect in this current study as it enhances the rate of heat transfer [49], (iv) performing the stability analysis in order to identify the stability of the solution since non-unique solution is expected to exist. This contribution may benefit the scientists and academicians and give add-on value to their expertise.…”
Section: Introductionmentioning
confidence: 99%